Proceedings of the 45th Annual Design Automation Conference 2008
DOI: 10.1145/1391469.1391535
|View full text |Cite
|
Sign up to set email alerts
|

Assertion-based verification of a 32 thread SPARC™ CMT microprocessor

Abstract: Exhaustive property checking, design defect isolation and functional coverage measurement are some of the key challenges of design verification. This paper describes how an assertion based approach successfully addressed these challenges for the verification of an enterprise class chip-multi-threaded (CMT) SPARC TM microprocessor. Methodology and experiences are discussed and recommendations are made on how to incorporate this into the design verification process. Experience with using assertion checks for for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In the worst case, the automaton can be exponential in the size of the property and the overhead of checking the property during simulation can be prohibitively expensive. In [24], it is reported that depending on the number and the kind of properties they express, property checking can degrade simulation speed anywhere from 25% to 100%.…”
Section: Discussion and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the worst case, the automaton can be exponential in the size of the property and the overhead of checking the property during simulation can be prohibitively expensive. In [24], it is reported that depending on the number and the kind of properties they express, property checking can degrade simulation speed anywhere from 25% to 100%.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…This is undesirable. Furthermore, the effort to maintain properties for an industrial design can often be very large [24] and cannot be under estimated.…”
Section: Introductionmentioning
confidence: 99%
“…can be monitored using assertions [94]. Turumella et al explored how assertions can be used to verify the control logic of an enterprise-class chip-multi-threaded SPARC TM microprocessor [105].…”
Section: Control Logic Verificationmentioning
confidence: 99%
“…Pellauer explored interface assertions in Bluespec System Verilog [87]. Turumella et al 's work captured inter-module interface assertions in the SPARC TM microprocessor as well [105].…”
Section: Design Interfacementioning
confidence: 99%
See 1 more Smart Citation